2010
DOI: 10.1002/pmic.201000228
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of A549 cells infected with human respiratory syncytial virus subgroup B using SILAC coupled to LC‐MS/MS

Abstract: Human respiratory syncytial virus (HRSV) is a leading cause of serious lower respiratory tract infections in infants. The virus has two subgroups A and B, which differ in prevalence and (nucleotide) sequence. The interaction of subgroup A viruses with the host cell is relatively well characterized, whereas for subgroup B viruses it is not. Therefore quantitative proteomics was used to investigate the interaction of subgroup B viruses with A549 cells, a respiratory cell line. Changes in the cellular proteome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 58 publications
4
59
0
Order By: Relevance
“…A549 cells have been extensively used in the characterization of metal exposure and in the proteomic analysis of cells [13] [44]. In our 2DE experiments, A549 cells were incubated with 100 µM ZnSO 4 and harvested after 24 h. This concentration and exposure time and concentration was chosen to ensure that the cells remained approximately 75% confluent without undergoing contact inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…A549 cells have been extensively used in the characterization of metal exposure and in the proteomic analysis of cells [13] [44]. In our 2DE experiments, A549 cells were incubated with 100 µM ZnSO 4 and harvested after 24 h. This concentration and exposure time and concentration was chosen to ensure that the cells remained approximately 75% confluent without undergoing contact inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Of particular interest were previously uncharacterised changes in the abundance of mitochondrial proteins quantified 24 h post‐infection (p.i.) in comparison to mock [5,10,11]…”
Section: Introductionmentioning
confidence: 99%
“…Identifying those cellular proteins critical for HRSV biology and disputing their activity could lead to broader spectrum antiviral compounds being developed: high throughput, quantitative proteomic analysis provides a powerful tool for identifying such intricate protein and pathway‐specific alterations in virus‐infected cells on a large scale [9]. Previous global proteomic analyses of HRSV–host cell interactions highlighted specific cellular proteome changes related to the antiviral response and demonstrated that host cell proteome alterations were confined to specific signalling pathways and processes [5,10,11]. Of particular interest were previously uncharacterised changes in the abundance of mitochondrial proteins quantified 24 h post‐infection (p.i.)…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock protein 70 (Hsp70) was also identified and found to have an increased abundance in lipid-raft membranes [125]. nucleolus and ND10, were validated by Western blot and indirect immunofluorescence confocal microscopy analysis, respectively [131]. Flotation gradient analysis confirmed the increased level of raft-associated Hsp70 and immunoprecipitation assays validated the interaction between Hsp70 and virus polymerase complex in lipid-rafts [126].…”
Section: Human Respiratory Syncytial Virus (Rsv)mentioning
confidence: 90%